Canonical Perspective on Social Justice and Charity - Lourdusamy, Sahayaraj (Studia canonica, 2015)
As Pope Benedict XVI says, the nature of the Catholic Church is expressed in its three-fold responsibility: of proclaiming the word of God (kerygma-martyria), celebrating the sacraments (leitourgia) and exercising the ministry of charity (diakonia). These duties presuppose each other and are inseparable. The service of charity is also a constitutive element of the Church’s mission and an indispensable expression of its very being. The works of charity especially towards the poor and the needy are to be the chief concern of the Catholic Church in the modern world and for this purpose there should be specific regulations concerning the utilization of the goods of the Church. The two Codes, following the long tradition of Catholic social teaching, insist on the double obligation of all the faithful to promote social justice and charity. They also enlist the regulations for the proper administration of the temporal goods which are the ‘patrimony of the poor’. The vision and mission of the Catholic Church of promoting social justice and charity remind us the prophetic invitation of the Pope Francis for the Church to remain with the poor.